Literacy instruction for students who are deaf and hard of hearing - Easterbrooks, Susan R. (Professional perspectives on deafness., 2013)
Most students who are deaf or hard of hearing (DHH) struggle with acquiring literacy skills, some as a direct result of their hearing loss, some because they are receiving insufficient modifications to access the general education curriculum, and some because they have additional learning challenges necessitating significant program modifications. Additionally, instructional practices for DHH students tend to be directed toward two sub-populations of DHH students: those with useable access to sound and those without.